2017
DOI: 10.1155/2017/7686540
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Sea Breeze Convergence over Antarctic Peninsula

Abstract: The convergence zone induced by sea breeze systems over Antarctic Peninsula is analyzed for the summer season of 2013–2015. 59 days, selected by satellite images for the absence of major synoptic forcing, are simulated using the WRF model. Sea breeze convergence has been detected in 21 of these days, mostly during evening hours and under large-scale winds. Breeze events are associated with a cold anomaly at the peninsula with respect to the climatology. This condition favors the onset of the necessary horizont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…The back trajectories in this study are mainly used for the generation of density maps, to indicate the extent of reginal coverage by air masses for each of the flow classifications. At this resolution, sea breezes are expected to not be captured to their full extent, as previous numerical studies of sea breezes have used horizontal resolutions of 3 km (Comin and Acevedo, 2017) and 1 km (Arrillaga et al, 2016).…”
Section: Back Trajectory Analysis and Mean Sea Level Pressure Mapsmentioning
confidence: 99%
“…The back trajectories in this study are mainly used for the generation of density maps, to indicate the extent of reginal coverage by air masses for each of the flow classifications. At this resolution, sea breezes are expected to not be captured to their full extent, as previous numerical studies of sea breezes have used horizontal resolutions of 3 km (Comin and Acevedo, 2017) and 1 km (Arrillaga et al, 2016).…”
Section: Back Trajectory Analysis and Mean Sea Level Pressure Mapsmentioning
confidence: 99%
“…Muitos estudos foram realizados para investigar o desempenho do modelo WRF na Antártica, para períodos de alguns dias até escalas anuais, como por exemplo, Powers (2007), Tastula & Vihma (2011), Bromwich et al (2013, Comin & Acevedo (2017). Esses autores encontraram para a temperatura a 2 m da superfície uma correlação variando entre 0,51 a 0,90 e REQM entre 1,3 a 8,1°C.…”
Section: Introductionunclassified
“…Meanwhile, with the help of a nonhydrostatic mesoscale model, Stivar et al showed that lake breezes caused by the differences in the lake-land temperatures had significant effects on the local circulation in the Itaipu Lake area [13]. Recently, the state-of-the-art Weather Research and Forecasting (WRF) model was applied to simulate the complex structures of low atmosphere flow fields [14][15][16].…”
Section: Introductionmentioning
confidence: 99%